Evaluation of the Implementation of the Merdeka Curriculum at Vocational High School Using CIPP Model - M. Dimas Setiawan S.,; Tee Tze Kiong,; Hikmahyanti,; Charanjit Kaur Swaran Singh,; Rizky Ema Wulansari,; M. Aris Ichwanto, (Online Journal for TVET Practitioners, 2024)
As per the directive of the head of the ministry of education, culture, research, and technology (number 044/H/KR/2022) regarding educational units implementing Merdeka Curriculum implementation, the Merdeka Curriculum is scheduled to be implemented beginning with the 2022/2023 school year. Researchers employ Stufflebeam's CIPP evaluation approach, which includes context, input, process, and product components, to determine whether the new curriculum has been implemented appropriately and successfully. In Sumbawa, 310 students from vocational schools and 303 teachers participated in this study. The Merdeka Curriculum has been applied well in terms of context, input, process, and outcomes, according to this study, which used survey technique and a quantitative research approach. Researchers discovered that the average context score for instructors was 4.08, the average input score for teachers was 4.03, the average process score for teachers was 3.89, the average output score for teachers was 4.16, and the average student score was 4.00. It was discovered that, aside from that, there were statistically significant values in terms of the context of the teacher (Md = 4.00, n = 303) and the student (Md = 3.56, n = 310), the process of the teacher (Md = 3.86, n = 303) and the student (Md = 4.00, n = 310), the value of U = 38310.000, ? =.000, r =.000 while the Product of the instructor (Md = 4.29, n = 303) and the pupil (Md = 4.00, n = 310), U = 30985.000, ? =.000, and r =.000 are obtained. The results of the Mann Withney U-test, however, indicated that the teacher's (Md = 4.00, n = 303) and student's (Md = 4.00, n = 310) inputs were not statistically significant (U = 44775.000, ? =.307, r =.041). To ensure that teachers and students have the same understanding of context, input, process, and product, it is intended that the Merdeka Curriculum may be implemented more effectively.